Heat-Shocked Monocytes Are Resistant to Staphylococcus aureus-Induced Apoptotic DNA Fragmentation due to Expression of HSP72 - Guzik, Krzysztof (American Society for Microbiology, 1999)
Human peripheral blood monocytes became apoptotic following phagocytosis of Staphylococcus aureus. The consequences of heat stress for monocytes were studied with regard to the effect on S. aureus-induced apoptosis. Exposure of monocytes to 41.5°C for 1 h resulted in HSP72 expression and had no influence on phagocytosis of bacteria; moreover, phagocytosis of S. aureus immediately or shortly after heat shock had no effect on the S. aureus-induced monocyte apoptosis, as evidenced by DNA fragmentation assay. In contrast, cells which recovered from heat shock for 18 to 24 h, although active as phagocytes, were resistant to the S. aureus-induced apoptosis. The observed protective effect was related to the induction of HSP72, since blocking of HSP72 synthesis by an antisense oligomer abolished the protective effect of heat shock on bacterium-induced monocyte apoptosis.